Management of Active Records in Referral Hospitals: A Case Study of Kisoro Hospital. - Hashakimana, Obed (Kabale University, 2024)
This research was carried out under the topic "management of active records in Referral Hospitals. The case study was Kisoro Hospital. Interview and observation methods were used 18 respondents were involved in the data collection. These included; three records officers, seven Nurses, and eight patients. The data was collected, analyzed, and computed to determine the challenges records departments meet in their daily activities resulting from their storage types of equipment usage. The result of the study showed that most hospitals still use old-fashioned storage types of equipment and computers are still rare in the Records departments' offices. Although it was noticed that records officers knew their roles and responsibilities, they still needed constant workshops and training to keep them up-to-date about advanced technology in keeping medical records. In conclusion, therefore, the storage types of equipment being used records department should be upgraded and computer networks are required for the smooth running of daily activities. According to (Parish Paud: 1990), it is advisable to seek the assistance of a knowledgeable consultant when setting up and monitoring such a project as managing and maintaining active records. Finally, it is premature for any, except the most sophisticated depositaries with highly trained personnel to consider digitization. While much has been learned by several project impacts, too little is known about archiving cost transferability of data and other factors to make it a practicable option for the ordinary repository (Parish Paud: 1990)